Pengaruh Pembinaan Latihan Fisik Jasmani Guna Meningkatkan Kemampuan Militer Perorangan Dalam Menjamin Kesiapan Tugas Operasional TNI - Nugroho, Arif (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Physical training is a key element in improving individual military capabilities to ensure the TNI's operational task readiness. With the heavy physical and mental demands of many military operations, it is important to ensure that physical training programs are designed and implemented effectively. This research aims to evaluate the effect of physical training on individual military abilities. The method used was quantitative involving 50 respondents from various military units. The research instrument includes a questionnaire which was tested for validity and reliability. The validity test results show that all question items are valid, with an item-total correlation value between 0.68 to 0.85, and a Cronbach Alpha coefficient of 0.87 for the physical training development variable and 0.82 for individual military ability, indicating high reliability. Linear regression analysis produces a non-standardized regression coefficient of 0.45 and a Beta of 0.60, with a t value of 4.50 and a significance of 0.000, indicating a significant influence of physical training on military capability. The regression coefficient test also revealed an F value of 20.00 with a p-value of 0.000, confirming the significance of the overall regression model. These findings indicate that physical training training programs significantly increase soldiers' endurance, strength, and mental readiness, supporting their effectiveness in carrying out military duties.